Sosialisasi Pembuatan Nugget Singkong sebagai Alternatif Menu Sehat Bagi Balita Stunting di Desa Sedayu Kabupaten Klaten - Putri, Dwi Tiga; Kuatno, Sri; Sitompul, Andriyan Lopes; Diyahwati, Diyahwati; Fitria, Annisa Noor (Jurnal Bina Desa, 2024)
One of the efforts made by the Klaten Regency government to reduce the number of stunting is establishing Baby Café as a provider of baby porridge with complete nutritional content of the toddlers. One of the villages that already has a Baby Café is Sedayu. Enterprising UNNES GIAT 7 Sedayu stundents saw the opportunity for Baby Café as a very targeted means og utilizing local food sources fpr stunted toddlers. One the the potentials found in Sedayu Village is casava which is widely grown, but not yet widely processed into various foods. Therefore, UNNES GIAT 7 students innovated cassava nuggets as a form of utilizing local food sources that children can enjoy. The implementation method was carried out using observation which was then continued with a nugget demonstration with baby café administrators who were accompanied by the village head and village midwife, the developed with the assistance of a baby café to be able to sell cassava nuggets and ended with distributing cassava nuggets form house to house to toddlers who were stunted.